OIL PRICE SHOCKS AND NIGERIAN ECONOMIC GROWTH - Ibrahim Alley; Ayodele Asekomeh; Hakeem Mobolaji; Yinka A. Adeniran (European Scientific Journal, ESJ, 2014)
This study employs the general methods of moment (GMM) to examine the impact of oil price shocks on the Nigerian economy, using data from 1981 to 2012. After appropriate robustness checks, the study finds out that oil price shocks insignificantly retards economic growth while oil price itself significantly improves it. The significant positive effect of oil price on economic growth confirms the conventional wisdom that oil price increase is beneficial to oil-exporting country like Nigeria. Shocks however create uncertainty and undermine effective fiscal management of crude oil revenue; hence the negative effect of oil price shocks.